Germplasm screening and genetic improvement - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1981)
Research work carried out by CIAT in 1980 and results obtained are briefly analyzed: acquisition, evaluation, and distribution of germplasm; bush and climbing bean improvement; resistance to viral (BCMV, BYMV, soybean mosaic virus, bean chlorotic mottle virus, and BGMV), fungal (rust, anthracnose, and angular leaf spot), and bacterial diseases (bacterial blight and halo blight), and to pests (Empoasca kraemeri and Tetranychus desertorum); yield and plant architecture; tolerance to moderately acid soils and water stress; variability from interspecific hybridization; N fixation; nutritional and quality factors; bean flour manufacture. Two appendixes are included: (1) detailed description of Phaseolus vulgaris growth habits and (2) list of CIAT accessions of Phaseolus referred to in this report, including CIAT no. of accession, identification, local register, and source. (CIAT)